2009
DOI: 10.1002/ange.200904635
|View full text |Cite
|
Sign up to set email alerts
|

A Multinuclear Coordination System of L‐Cysteine and L‐Penicillamine That Induce Opposite Chiralities at Metal Centers

Abstract: Gleich und doch verschieden: L‐Cystein (L‐Cys) und L‐Penicillamin (L‐Pen) bilden die gleichen fünfkernigen AuI3M2‐Strukturen (M=NiII, CoIII) mit allerdings umgekehrten Konfigurationen. Als Ursache für dieses Phänomen werden intramolekulare Wasserstoffbrücken und sterische Wechselwirkungen vermutet, die auch erklären könnten, weshalb sich in der Natur D‐Penicillamin wie L‐Cystein verhält.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…[14] We have been interested in the diastereoselective synthesis of polynuclear and supramolecular coordination compounds by employing chiral sulfurcontaining amino acids, such as cysteine (H 2 cys) and penicillamine (H 2 pen). [15][16][17] Recently, we have shown that a linear Au I complex with…”
mentioning
confidence: 99%
“…[14] We have been interested in the diastereoselective synthesis of polynuclear and supramolecular coordination compounds by employing chiral sulfurcontaining amino acids, such as cysteine (H 2 cys) and penicillamine (H 2 pen). [15][16][17] Recently, we have shown that a linear Au I complex with…”
mentioning
confidence: 99%